Spelling bee contest UiTM Mukah - Rijeng, Jacqueline Susan (Universiti Teknologi MARA, Sarawak, 2017)
It was indeed a memorable evening for the students who took part in the Spelling Bee Contest held at Dewan Sri Balau, Kampus Mukah on 13 February 2017. Out of the 45 students from different programmes who took part in the preliminary round, only 16 contestants managed to get themselves shortlisted for the final. The main objectives of the competition were to help students improve their spelling, enhance their vocabulary and develop correct English usage. The competition was officiated by Mr Musa bin Bohari, (Head, Centre of Business and Management Studies) followed by a graceful welcoming performance by HPD221 - Public Speaking II students. Four esteemed judges from the Academy of Language Studies were involved in the competition under two categories namely the Individual and Group Categories. Winners of both categories took home cash prizes worth RM100 (Champion), RM70 (2nd runner-up) and RM50 (3rd runner-up). The competition received positive responses from students and it is hoped that more such competitions will be held in the coming semester. Sincere appreciation goes to the students taking HPD221 - Public Speaking II in the present semester for successfully organising the contest.